Placenta accreta and posterolateral uterine wall rupture in first trimester in multiparous woman with scarred uterus with history of intake of misoprostol and mifepristone: a case report - Surjyatapa Bhattacharjee; Pranoy Nath; Sereesha Rao (Barpeta Obstetrics and Gynaecological Society, 2022)
Uterine rupture is a life threatening complication which may lead to significant mortality and morbidity. Posterior wall uterine rupture is a rare presentation especially in the first trimester. Abnormal placental attachment is, similarly, a rare phenomenon, diagnosed chiefly in 3rd trimester. The co-existence of uterine rupture with abnormal placentation in first trimester is extremely rare. Here in, we experienced a case of posterior uterine wall rupture in a 32-year-old gravida 4 para 2 pregnant woman with history of one spontaneous abortion. The patient presented at gestational age of 10 weeks with acute abdomen and severe anemia. She had history of two lower segment caesarean sections. Also, there was history of intake of mifepristone and misoprostol a month back. Ultrasonographic findings were suspicious towards heterotopic pregnancy. However, abdominal exploration revealed posterolateral uterine wall rupture away from the site of lower segment cesarean scar with adherent placenta at the site of scar. Subtotal hysterectomy was done. The patient was discharged 5 days later after transfusion of 4 units packed red blood cells.